Impression Management in the Job Interview: An Effective Way of Mitigating Discrimination against Older Applicants? - Gioaba, Irina; Krings, Franciska (Frontiers in Psychology, 2017)
The increasingly aging population in most industrialized societies, coupled with the rather age-diverse current workforce makes discrimination against older employees a prevalent issue, especially in employment contexts. This renders research on ways for reducing this type of discrimination a particularly pressing concern. Drawing on theories of social identity and impression management, our research examines the role of impression management, aimed at refuting common older worker stereotypes, in diminishing bias against older job applicants during the job interview. The study consisted in an experimental hiring simulation conducted on a sample of 515 undergraduate students. Results show that older applicants who used impression management to contradict common older worker stereotypes were perceived as more hirable than those who did not. However, despite this positive effect, discrimination persisted: older applicants were consistently rated as less hirable than their younger counterparts when displaying the same IM behavior. Taken together, this research demonstrates that older job seekers can indeed ameliorate biased interview outcomes by engaging in impression management targeting common age stereotypes; however, it also shows that this strategy is insufficient for overcoming age discrimination entirely. The current study has important implications for theory, by expanding research on the use of impression management in mitigating age discrimination, as well as for practice, by offering older employees a hands-on strategy to reduce bias and stereotyping against them.